Promoting the good life and preventing the bad: what impact does the language used in legislation have on the provision of life-changing public services? a natural experiment of homelessness provision in England and Wales - Williams, M (Political Studies Association, 2018)
What are the consequences of including adjectives in legislation? Presenting a difference-in-differences analysis of a natural experiment, this paper demonstrates that the word ‘vulnerable’ had a strong and statistically significant effect on homelessness provision in England after 2002. When compared to Wales as a control group, comparator English local authorities identified using propensity score matching saw an average 81% drop in applying their duties to house. Using new panel data covering 728 local authority-years and testing four hypotheses under eight model specifications it will be shown that mixing legislative and natural languages significantly affects policy provision, even when controlling for political, financial and socioeconomic variables.